Legal and Cultural Analysis of Copyright Law Implementation for Street Musicians in Indonesia - Bataweya, Ardin; Hente, Julman; Kotyazhov, Andrey V.; Ovosi, Bilkisu Mohammed (Kawanua International Journal of Multicultural Studies, 2024)
This research examines the implementation of Copyright Law for street musicians in Indonesia, focusing on the intersection between legal protection and cultural practices. The phenomenon of street musicians performing cover songs creates tension between the formal legal framework and the tradition of sharing art in Indonesian culture, as seen in the cases of Tri Suaka and Zinidin Zidan. The research aims to analyze the effectiveness of Law Number 28 of 2014 in addressing copyright infringement while considering cultural practices, and to identify socio-cultural factors that influence legal compliance among street musicians. Using a qualitative approach with socio-legal research design, this study integrates legal analysis and cultural studies through systematic document review and case studies. The findings indicate that the effectiveness of copyright protection is heavily influenced by the complex interrelation between legal requirements and cultural traditions, where current implementation faces challenges in balancing formal compliance with the cultural significance of street performances. This research implies the need for developing a more adaptive legal framework, including special licensing systems and strengthening the role of Collective Management Organizations in supporting legal compliance while preserving culture.